Work-Life Balance and Intention to Stay: The Mediating Effect of Job Satisfaction Among Generation Z - Samirah Khairunnisa; Fetty Poerwita Sary (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of work-life balance on intention to stay, with job satisfaction as a mediator among Generation Z employees in Bandung Raya. Using a quantitative survey of 230 respondents, data were analyzed with PLS-SEM through SmartPLS 4.0. The results show that job satisfaction positively affects intention to stay and significantly mediates the relationship between work-life balance and intention to stay. However, work-life balance has a significant negative direct effect on intention to stay. These findings highlight job satisfaction as a key mechanism in explaining Generation Z employee retention. Keywords: Work-Life Balance; Intention to Stay; Job Satisfaction; Generation Z